GENERATION OF PORPHYRITIC AND EQUIGRANULAR MAFIC ENCLAVES DURING MAGMA RECHARGE EVENTS AT UNZEN VOLCANO, JAPAN - Browne B.L.; Eichelberger J.C.; Dehn J.; Patino L.C.; Vogel T.A.; Uto K.; Hoshizumi H. (My University, 2006)
Mafic to intermediate enclaves are evenly distributed throughout the dacitic 1991-1995 lava sequence of Unzen volcano, Japan, representing hundreds of mafic recharge events over the life of the volcano. This study documents the morphological, textural, chemical, and petrological characteristics of the enclaves and coexisting silicic host lavas. The eruptive products described in this study appear to be general products of magma mingling, as the same textural types are seen at many other volcanoes. Two types of magmatic enclaves, referred to as Porphyritic and Equigranular, are easily distinguished texturally. Porphyritic enclaves display a wide range in composition from basalt to andesite, are glass-rich, spherical and porphyritic, and contain large, resorbed, plagioclase phenocrysts in a matrix of acicular crystals and glass. Equigranular enclaves are andesitic, non-porphyritic, and consist of tabular, medium-grained microphenocrysts in a matrix glass that is in equilibrium with the host dacite magma. Porphyritic enclaves are produced when intruding basaltic magma engulfs melt and phenocrysts of resident silicic magma at their mutual interface. Equigranular enclaves are a product of a more prolonged mixing and gradual crystallization at a slower cooling rate within the interior of the mafic intrusion. © The Author 2005. Published by Oxford University Press. All rights reserved.
Keywords: MAFIC ENCLAVES; MAGMA MINGLING; QUENCHED MAFIC INCLUSIONS; RESORBED PLAGIOCLASE; UNZEN SCIENTIFIC DRILLING PROJECT; UNZEN VOLCANO